Global and countrywide prevalence of subclinical and clinical mastitis in dairy cattle and buffaloes by systematic review and meta-analysis. (May 2021) - Krishnamoorthy, Paramanandham; Goudar, Akshata Lokanath; Suresh, Kuralayanapalya Puttahonnappa; Roy, Parimal
Abstract: In the present study, subclinical mastitis (SCM) and clinical mastitis (CM) prevalence for various countries in the World were calculated by using online and offline databases. The SCM and CM prevalence studies reported during 1967-2019 were collected, reviewed, and a meta-analysis was done in R-Software. A total of 222 and 150 studies from the World and 103 and 37 studies from India on SCM and CM, respectively were included. The pooled prevalence of SCM and CM were 42% [Confidence Interval (CI) 38-45%, Prediction Interval (PI) 10-83%] and 15% [CI 12-19%, PI 1-81%] in the World respectively, 45% [CI 40-49%, PI 11-84%] and 18% [CI 14-23%, PI 3-60%] in India respectively. Continent-wise analysis indicated a higher prevalence of SCM in North America and CM in Europe and among the countries, a higher SCM prevalence in Uganda and CM in the United Kingdom was observed. Further, species-wise indicated a higher SCM and CM prevalence in buffaloes of the World than the cattle. Based on method-wise, SCM and CM prevalence were high in somatic cell count and clinical examination, respectively in the World. The SCM prevalence was higher than CM and indicated the importance of SCM in dairy cattle. This might result in low milk productivity in dairying and may set off losses to dairy farmers. Hence, there is an urgent need to reduce the SCM and CM prevalence by implementing scientific dairy management, good feeding practices, and timely therapeutic interventions for increasing the benefits from dairying to the farmers in the World. Highlights: Subclinical mastitis (SCM) and clinical mastitis (CM) prevalence were 42% and 15%, respectively, in the World. The SCM prevalence was higher when compared to CM prevalence in the countries of the World. California mastitis test and clinical examination were used for SCM and CM diagnosis, respectively in most of the studies. The prevalence estimates for SCM and CM were 45% and 18% in India. First report of SCM and CM prevalence estimates for the World by systematic review and meta-analysis.